Mucormycosis as the Elusive Cause of an Aortic Thrombus and Tissue-Obliterating Abscess - Shira R. Paul; Preston S. Gable (Case Reports in Hematology)
Invasive mucormycosis is an increasingly common cause of morbidity and mortality in hematologic malignancy patients. Early consideration of the diagnosis is essential in at-risk patients, exhibiting suggestive signs and symptoms. A 56-year-old female with acute myeloid leukemia initially presented with neutropenic fever before subsequently developing dense hemiplegia due to septic emboli to the spine and multifocal abscesses. These findings were later determined to be a result of a disseminated mucor infection and represented a rare manifestation of the disease. Despite the disseminated nature of the infection, identification of the causative organism was initially impeded by limitations in obtaining a tissue sample in a severely thrombocytopenic patient, as is common among hematologic malignancy patients. As a result of this limitation, diagnosis was ultimately made via PCR on bronchiolar lavage fluid. Early consideration of the diagnosis with prompt initiation of treatment is of utmost importance in this invasive infection. Further research is needed to identify and validate rapid, minimally invasive strategies for early diagnosis of mucormycosis.